2003
DOI: 10.1136/thorax.58.11.961
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophil apoptosis in the resolution of acute lung injury in newborn infants

Abstract: Background: The persistent airway neutrophilia observed in chronic lung disease of prematurity (CLD) may reflect inappropriate suppression of neutrophil apoptosis. Methods: 134 bronchoalveolar lavage (BAL) samples were obtained from 32 infants requiring mechanical ventilation for respiratory distress syndrome (RDS): 13 infants (median gestation 26 weeks, range 23 to 28) subsequently developed CLD (CLD group), and 19 infants (gestation 31 weeks, range 25 to 39) recovered fully (RDS group). A further 73 BAL samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 40 publications
2
53
1
2
Order By: Relevance
“…[11][12][13] Most recently, a prolonged survival of neonatal neutrophils owing to an inappropriate suppression of neutrophil apoptosis has been described. [14][15][16] Before neutrophil migration, cellular attachment to endothelial cells is mediated through a complex interaction of adhesion molecules. Increased concentrations of various cellular and endothelial adhesion molecules such as intercellular adhesion molecule (ICAM-1) and selectins have been detected in airway secretions and the circulation of preterm infants with BPD.…”
Section: Inflammatory Cells Endothelial Interactions and Chemotaxismentioning
confidence: 99%
“…[11][12][13] Most recently, a prolonged survival of neonatal neutrophils owing to an inappropriate suppression of neutrophil apoptosis has been described. [14][15][16] Before neutrophil migration, cellular attachment to endothelial cells is mediated through a complex interaction of adhesion molecules. Increased concentrations of various cellular and endothelial adhesion molecules such as intercellular adhesion molecule (ICAM-1) and selectins have been detected in airway secretions and the circulation of preterm infants with BPD.…”
Section: Inflammatory Cells Endothelial Interactions and Chemotaxismentioning
confidence: 99%
“…Post-natal inflammatory response dominated by persistent neutrophil activity [25] and the presence of oxidative stress, may play a major role in this process since both are known to alter eNO [7,8]. Neutrophil activity and oxidative stress both promote the oxygenation of NO to soluble peroxy-nitrites, nitrites and nitrates.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…The etiology of this CLD of premature infants is unclear and has been associated with a myriad of risk factors (14,15). Persistence of lung PMN is one characteristic associated with CLD; however, whether a delay in the apoptosis of these PMN contributes to their persistence, as has been suggested, has not been established (16,17).…”
mentioning
confidence: 99%
“…Several recent studies have shown delayed apoptosis of lung PMN in premature neonates at risk for developing CLD (16,17), although the involved mechanisms remain to be defined. In previous in vitro studies, we observed that neonatal PMN had an intrinsic delay in both spontaneous and Fasmediated apoptosis (18), which was associated with decreased activity of caspase-3 (52), a critical downstream mediator of PMN apoptosis (53).…”
mentioning
confidence: 99%